Be mindful in love: Exploring the interpersonal effects of spouse mindfulness on employee work and family outcomes. Issue 2 (9th September 2021) - Zheng, Xiaoming; Ni, Dan; Zhu, Jinlong; Song, Lynda Jiwen; Liu, Xiao‐Yu; Johnson, Russell E.
Abstract: Mindfulness has received increasing attention from scholars and practitioners, and considerable research has demonstrated the intra personal effects of mindfulness at work or at home. Research to date, however, has overlooked potential inter personal effects of mindfulness across the work and family domains. Drawing on the spillover‐crossover model and the mindfulness literature, we investigate the effects of spouse mindfulness at home on employee work and family outcomes. We test our model using dyadic experience‐sampling data collected from 125 focal employees and their spouses over 10 consecutive workdays. The results indicated that, at the within‐person level, spouse mindfulness at home was positively associated with employee authentic emotional sharing at home, which, in turn, was positively associated with employee positive effect at home but negatively associated with employee negative affect at home. The results also indicated that spouse mindfulness at home had a positive indirect effect on family satisfaction at home and work engagement during the next morning through enhancing employee authentic emotional sharing at home. We discuss the implications of these findings and directions for the mindfulness research.